Facile preparation of hydrophobic polydimethylsiloxane based reusable oil-absorbents for effective oil/water separation - Kose, Ceyda; Kandemir, Merve; Kizil, Soner; Bayraktaroglu, Seda; Sonmez, Hayal Bulbul (Elsevier Science Inc, 2024)
Water pollution due to oil drilling, human mistakes, tanker accidents, and natural disasters have severely affected humanity. A rapid removal of such pollutants from the environment should be a priority. In this paper, polydimethylsiloxane-based polymer sorbents have been fabricated by using carbinol terminated polydimethylsiloxane (PDMS) and organosilicon cross-linker via the one-pot bulk polymerization method. The preparation method does not require any activator, solvent, initiator, or catalyst. Obtained cross-linked sorbents have a high interest in organic liquids and oils, while no interest in water mediums. Absorption kinetics also show that they can quickly absorb the oil into their porous structure in a short time, implying their effective use in sudden oil leakages. They can selectively absorb the oil from different water mediums repeatedly used without any significant capacity loss. The output demonstrated that PDMS-based cross-linked polymers could be effectively utilized as sorbents in the event of oil spillage in order to absorb the spilled oil from wastewater.
Keywords: Oil spill; Carbinol; Water pollution; Reusability; Polydimethylsiloxane